TINJAUAN MASLAHAH TERHADAP GBHN DALAM SISTEM PRESIDENSIAL - Rooby Pangestu Mulyo (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2023)
This article examines GBHN in the perspective of Maşlaĥah. This research uses a research method with a historical approach. The method of analysis used is the deductive method. The result of this research is that currently Indonesia does not need a GBHN, because Law Number 17 of 2007 concerning the National Long-Term Development Plan and Law Number 25 of 2004 concerning the National Development Planning System have been in effect and have become important development references, it is only how a President organizes the structures under him in development affairs so that the expected development can be achieved. On the other hand, in terms of the concept of Maşlaĥah, the discourse of reviving the GBHN will have an impact on the lack of responsibility of a state leader towards his people and of course it will be a problem because there are citizens' rights that are not fulfilled